The THE STUDY OF STUDENTS’ ABILITY IN MASTERING THE MAIN IDEA AND THE SUPPORTING IDEA IN PARAGRAPH TO THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 2 BENDAHARA ACEH TAMIANG - makhroji - - (Journal of Education, Linguistics, Literature and Language Teaching, 2018)
The writer took this school as the place of her research, because she wanted to know about the ability of the students in differentiating the main ideas and the supporting idea in paragraph especially to the eleventh grade students. There are many problems faced by the students in differentiating the main ideas and the supporting idea in paragraph. If the students can not find the main ideas, they will get problems to understand the English text, where in learning process, they found many text in their lesson. The writer has the purposes in this study, to know how far their ability in differentiating the main ideas and the supporting idea in paragraph, to know whether the students have the good structure in writing and to know the influence of the teacher to make the students know and also can make the good paragraph. After doing research from the questioners, and test for collecting data, which uses the formula of statistic, namely the students have very good ability is 12% only 5 students, good ability is 28% with 11 students, moderate is 50% is 19 students and fair ability is 10 % with 4 students.. Finally, the writer can make the conclusions in her research that there are many correlations between the main ideas and the supporting idea in paragraph, the students are rather difficult to differentiate and understand about the main ideas and supporting idea. The students who got very good ability is still few people. The suggestion maybe the students should ask the teacher if they do not understand about the main ideas and the supporting idea.